The meaning of normative pedagogy in contemporaniety - Komar, Zvonimir (Array, 2009)
The question that precedes any contemplation regarding meaning of normative pedagogy, especially today, has to be «Why normative pedagogy?». In this segment of our work, we'll try to investigate the meaning of norm as such, while distancing ourselves from the usual concept of merely (often theoretically unfounded) «setting norms». The whole question is «Where are the norms set from?», and what norm itself truly is. There are two fundamental ways of thought regarding this issue: heteronomous, where norm is not viewed as norm per se, and is set with externally defined purpose, while the other way is «setting norm» from its very own idea. Setting norm from its idea is founded upon specific ontological concepts, which will be explicated in the paper. Therefore, normativity will not be investigated from the viewpoint of educational politics, society management and control and other external, in relation to idea of norm itself heteronomous and most frequently ideological sources, but from the idea of norm as such and from that which enables its very existence and makes/doesn't make it necessary for a science such as pedagogy. Then, we shall investigate the mutual relation of ideas of normativity and pedagogy, with particular accent to question «Is pedagogy without normativity even possible?». The «especially today» part of first sentence of this summary already points out at a very specific condition of anything «normative» in contemporaniety. To try and see through this relation, the work shall try to elaborate further on the previously determined meaning of normative pedagogy and see it in the context of contemporary theory in general sense, which will be the fundament for understanding the idea of contemporaniety. From results of these contemplations we shall further try to see the possibility of connection between normative pedagogy and contemporaniety. If we manage to see this connection, the (in)significance of normative pedagogy (or pedagogy itself?) for contemporary time which does not question itself and takes itself as a positivistic fact should become evident, just as reasons for prevailing abandonment, ignoring, or attitudes towards normative pedagogy as being «irrelevant» or «totalitarian».